Improving Pronunciation with Phonetics-Based Teaching Strategies - Babaxanova Dildora Ikromjon qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
Effective pronunciation is a crucial aspect of language learning, influencing intelligibility and communication skills. Phonetics-based teaching strategies provide structured approaches to improve learners’ pronunciation by focusing on sound articulation, stress, rhythm, and intonation. This article explores various phonetics-based strategies for teaching pronunciation in English as a Foreign Language (EFL) classrooms. It discusses theoretical foundations, practical applications, and challenges associated with these strategies. The findings highlight the benefits of integrating phonetic instruction into language teaching to enhance learners' spoken proficiency and confidence.